Formation and magnetic properties of spark plasma sintered Mn3−δGa (δ = 0, 1) Heusler alloys: Experiment and theory. (July 2021) - Perween, Sonam; Rathi, A.; Raghuvanshi, Parul Rani; Bhattacharya, Amrita; PrakashMadduri, P.V.; Rout, P.K.; Sivaiah, B.; Dhar, Ajay; Pant, R.P.; Gahtori, B.; Basheed, G.A.
Abstract: In this study, we synthesized D022 Mn3− δ Ga ( δ  = 0, 1) alloys using the spark plasma sintering method. The m (T) results confirmed the formation of the D022 phase with Tc ≃ 780 K (710 K) for Mn3 Ga (Mn2 Ga). The alloys exhibited hard magnetic behavior with large room temperature spontaneous magnetization of m s (80 kOe) = 1.63 (0.83) μ B /f.u. and coercivity of Hc  = 4.28 (3.35) kOe for Mn3 Ga (Mn2 Ga). The magnetic properties were investigated further up to Tc and Hc (T) analysis using the Stoner–Wohlfarth model demonstrated the nucleation mechanism for the magnetization reversal. Calculations of the electronic density of states confirmed the magnetic contribution from two symmetrically inequivalent Mn sites in a Heusler-like tetragonal phase. Density functional theory calculations also showed that the ground state of D022 Mn2 Ga was achieved by the removal of Mn atoms from the full Heusler Mn3 Ga structure in accordance with the half-Heusler alloy structure, which supported the experimental observations. Highlights: Mn–Ga alloys synthesized by SPS. DFT identified ground state magnetic structures. Alloys exhibited hard magnetic behavior at room temperature.